2005
DOI: 10.1073/pnas.0503976102
|View full text |Cite
|
Sign up to set email alerts
|

Counting human somatic cell replications: Methylation mirrors endometrial stem cell divisions

Abstract: Cell proliferation may be altered in many diseases, but it is uncertain exactly how to measure total numbers of divisions. Although it is impossible to count every division directly, potentially total numbers of stem cell divisions since birth may be inferred from numbers of somatic errors. The idea is that divisions are surreptitiously recorded by random errors that occur during replication. To test this ''molecular clock'' hypothesis, epigenetic errors encoded in certain methylation patterns were counted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
98
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(111 citation statements)
references
References 15 publications
13
98
0
Order By: Relevance
“…'Type A' methylation was actually highest in elderly normal patients, whereas those with colorectal adenomatous lesions had significantly lower levels of 'type A' methylation. The positive correlation between 'type A' methylation and age supports the concept that 'type A' methylation reflects the mitotic 'age' of a tissue, an epigenetic record of cell turnover (Ahuja et al, 1998;Ahuja and Issa, 2000;Issa et al, 2001;Kim et al, 2005). Thus, 'type A' methylation, rather than being a prelude to cancer (Issa et al, 1994;Ahuja et al, 1998;Ahuja and Issa, 2000), might represent a component of 'normal' aging.…”
Section: Discussionsupporting
confidence: 57%
“…'Type A' methylation was actually highest in elderly normal patients, whereas those with colorectal adenomatous lesions had significantly lower levels of 'type A' methylation. The positive correlation between 'type A' methylation and age supports the concept that 'type A' methylation reflects the mitotic 'age' of a tissue, an epigenetic record of cell turnover (Ahuja et al, 1998;Ahuja and Issa, 2000;Issa et al, 2001;Kim et al, 2005). Thus, 'type A' methylation, rather than being a prelude to cancer (Issa et al, 1994;Ahuja et al, 1998;Ahuja and Issa, 2000), might represent a component of 'normal' aging.…”
Section: Discussionsupporting
confidence: 57%
“…Conversely, abandoned are epigenetic changes emerging from more mature descendant cells presumably present in the functionalis endometrium when these cells are lost during menstruation. Kim et al (2005) analysed the methylation patterns found in individual glands derived from cycling and atrophic human endometrium mathematically, substantiating the idea that there exists a stem cell niche in an individual gland. Furthermore, an undetermined number of stem/progenitor cells with long life span, but not a single stem cell, may be present in each niche (Kim et al 2005).…”
Section: Stem/progenitor Cells In Human Endometriummentioning
confidence: 95%
“…Investigation of methylation patterns in individual endometrial glands is one of the retrospective approaches for studying the activity of endometrial stem/progenitor cells (Kim et al 2005). A 'cellular history' encoded by epigenetic variations in individual glands reflects the methylation patterns arising from stem/progenitor cells, because such epigenetic changes are thought to be transmitted to daughter cells.…”
Section: Stem/progenitor Cells In Human Endometriummentioning
confidence: 99%
“…are also found in surface epithelial cells that are not menstruated in the mouse [125]. SP cells are found in the stratum basalis of human endometrial glands [125] and, based upon DNA methylation patterns, individual glands, like intestinal crypts, appear to be populated by multiple stem cells [126].…”
Section: Female Reproductive Tractmentioning
confidence: 99%